0513 Comparison of Patient Satisfaction and Therapeutic Alliance for Telemedicine vs. Face-to-Face Delivered Cognitive Behavioral Therapy for Insomnia. (27th May 2020) - Conroy, D A; Mooney, A; Pace, D; Balstad, S; Dubuc, K; Yang, A; Furgal, A; Sen, A; Arnedt, J
Abstract: Introduction: CBT for insomnia (CBTI) is effective but a barrier to its widespread use is the lack of evidence-based delivery modalities other than face-to-face. The perception and acceptability of telemedicine for the delivery of CBTI is unknown. We conducted a randomized controlled non-inferiority trial comparing face-to-face (F2F) and telemedicine (via AASM SleepTM) delivery of CBTI. We compared measures of patient satisfaction with treatment and the perception of the therapist's warmth and skills between F2F and SleepTM. Methods: Adults with insomnia were recruited from insomnia clinics and the community and screened for sleep, medical, and mental health disorders. Eligible participants were randomized to receive CBTI either via AASM SleepTM or F2F in 6 weekly sessions of 45-60 minutes each. Participants completed the Client Satisfaction Questionnaire (CSQ-8) and The Therapy Evaluation Questionnaire (TEQ) after completing treatment. The CSQ-8 score ranges from 8-32 with high scores indicating greater satisfaction. We also analyzed the two items on the TEQ that assess participants' perception of therapist's warmth and skills. Item scores ranged from 1-7, with higher scores indicating greater warmth and skills. Results: Sixty-five adults with chronic insomnia were recruited primarily from insomnia clinics. Sixty-two participants (41 women, mean age 48.9 ± 15.4 years) completed all 6 sessions of CBTI via F2F (n=32) or via AASM SleepTM (n=30). Independent samples t-tests revealed no significant differences between conditions on patient satisfaction (SleepTM, 28.5 +/-4.2 vs F2F 29.9 +/-2.4, t(-1.5), p=.14), therapist warmth (SleepTM, 6.0 ± 1.1 vs F2F, 6.4 ± 0.95, t(-1.4), p=.16), or therapist skills (Sleep TM 6.4 ± 1.0 vs F2F, 6.7 ± 0.59, t(-1.5), p=.15). Conclusion: Our findings suggest no differences in patient satisfaction, perception of therapist's warmth, or confidence in therapist's skills between telemedicine (via the AASM SleepTM) and F2F delivery of CBTI. Telemedicine-delivered CBTI should be implemented more widely. Support: Research supported by American Sleep Medicine Foundation Grant # 168-SR-17 (JT Arnedt)